Lautenistinnen in Deutschland im 18. Jahrhundert - Per Kjetil Farstad (Early Modern Culture Online, 2018)
"Lautenistinnen in Deutschland im 18. Jahrhundert" contains a descriptive presentation of some of the most outstanding female lutenists in the 18th Century German Countries: Luise Adelgunde Victoria von Gottsched, Anna Maria Wilhelmina von Althan Lobkovitz, Christiane Mariane von Ziegler, Anna Ilsabe Lehmann Brockes, and Friederike Sophie Wilhelmine of Bayreuth. The article is a small contribution to the ongoing international female research within the area of musicology. Key words:·      Women lutenists ·      18th century German Countries